A Juridical Review of the Implementation of Regional Regulation Number 5 of 2020 on Waste Management in Jambi Province - Maryani, Maryani; Riani, Ditasya Anisa; Larusji, Andi Muhammad; Gaos, Raden Deddy Wardana; Bilgufron, Bilgufron (International Journal of Business, Law, and Education, 2025)
This study aims to analyze the implementation of Jambi Provincial Regulation Number 5 of 2020 on Waste Management from a juridical perspective and to assess its effectiveness in achieving sustainable waste governance. The research employs a normative juridical approach by examining legal frameworks, documents, and secondary data related to the implementation of the regulation. Findings reveal that although the regulation comprehensively delineates the responsibilities of local governments, communities, and business actors, its implementation remains hampered by weak institutional coordination, limited infrastructure, and low public legal awareness. Therefore, improving inter-agency coordination, providing adequate waste management facilities, and enforcing legal sanctions consistently are crucial steps toward achieving effective and sustainable waste management.